INVESTING IN CHP PLANTS: ESTIMATING EXTERNAL COSTS AND BENEFITS (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: The purpose of this paper is to identify and evaluate the environmental impacts and estimate the external costs and benefits of building and operating a combined heat and power (CHP) plant. This research will contribute to the scientific literature in the field of public capital investments in CHP plants and facilitate the evaluation of similar assessments and studies by identifying relevant factors that affect society and the environment.Methodology: The ExternE methodology and Impact Pathway Approach (IPA) were used to estimate the externalities of building and operating the plant. The ExternE methodology considers environmental impacts, global warming impacts and accidents, and it is widely accepted in the estimation of externalities of CHP plants.Results: The main external benefits refer to the savings from the reduction of CO2 emissions per unit of energy produced, savings from the reduction of energy losses in the transmission of electricity, reduction of Croatia’s dependence on electricity imports, improvement of the balance of payments, and fiscal benefits. The main external costs arise from Croatia’s increasing import dependence on natural gas and changes in the use of agricultural land.Conclusion: It is estimated that the external benefits are higher than the external costs. In addition to the estimation of external costs, their internalization is done through various taxes and fees, thus affecting the unit cost of electricity. Further research should extend the estimation of external benefits and costs to consider broader social impacts and conduct a full cost-benefit analysis.